Transport Thailand papers presented at the conference sponsored by HM Government Department of Transport, the Institution of Civil Engineers and the British Overseas Trade Board : Bangkok, 29 November-2 December 1982. (Thomas Telford, 1982)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in Bangkok in 1982.